Analysis of Trends in Library Archive Digital Management from 2019 to 2023 - Rosyani, Widha; Yuadi, Imam (Jurnal Adabiya, 2024)
This research aims to understand and find problems related to managing library digital archives using bibliometric analysis. Bibliometric analysis was carried out on journals on the topic "Library Digital Archive" taken from the Web of Science (WoS) which produced 3,211 overall results, then filtered again according to the period from 2019 to 2023 producing 847 data and 500 data were taken for bibliometric analysis. To overcome and minimize risks arising from digital library archives using biblioshiny applications related to literature from 2019 to 2023. Analysis of journals related to library digital archives requires adjustments to archive management to digital form following advances in information technology, by using the flowchart method to carry out bibliometric analysis to provide emphasis during training or formulating policies, to expand knowledge about library digital archives to obtain positive results from adapting information technology and trends related to library digital archive management.------------------------------------------------------------------------------------------------Penelitian ini bertujuan memahami dan menemukan permasalahan terkait pengelolaan arsip digital perpustakaan menggunakan analisis bibliometric. Analisis bibliometrika dilakukan terhadap jurnal mengenai topik “Library Digital Archive” yang diambil dari Web of Science (WoS) yang menghasilkan 3.211 untuk hasil keseluruhan, kemudian difilter kembali sesuai periode muali 2019 sampai 2023 menghasilkan data sebanyak 847 dan diambil 500 data untuk dianalsis bibliometrik. Guna mengatasi dan meminimalisir resiko yang timbul dari adanya arsip digital perpustakaan dengan menggunakan aplikasi biblioshiny terkait literatur tahun 2019 sampai 2023. Analisis jurnal terkait arsip digital perpustakaan memerlukan penyesuaian pengelolaan arsip ke bentuk digital sesuai kemajuan teknologi informasi. Dengan menggunkan metode flowchart untuk melakukan analisis bibliometric guna memberikan penekanan saat pelatihan ataupun merumuskan kebijakan, untuk memperluas ilmu pengetahuan tentang arsip digital perpustakaan guna memperoleh hasil positif dari adaptasi teknologi informasi dan tren terkait pengelolaan arsip digital perpustakaan.